Oscillation criteria for nonlinear inhomogeneous hyperbolic equations with distributed deviating arguments. (1996) - Liu, Xinzhi; Fu, Xilin
Abstract : This paper investigates the oscillatory properties of solutions of nonlinear inhomogeneous hyperbolic equations with distributed deviating arguments subject to two different boundary conditions. Several oscillation criteria are establishing employing Green's Theorem and certain differential inequalities. An example is also given.